Equivalent Simulation: A Conversation with John Opera. - LaRocca, David (Afterimage)
An interview with photographer John Opera is presented. Topics discussed include his revival of older photographic processes including the anthotype and the cyanotype, how his work is informed by the uncertainty principle of physicist Werner Heisenberg, and the relationship between photography and painting. Works including the 2007 photograph "Baraboo" are cited.